2012
DOI: 10.1038/ejhg.2012.203
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of occult paragangliomas in asymptomatic carriers of SDHD and SDHB gene mutations

Abstract: Hereditary paraganglioma is a benign tumor syndrome with an age-dependent penetrance. Carriers of germline mutations in the SDHB or SDHD genes may develop parasympathetic paragangliomas in the head and neck region or sympathetic catecholamine-secreting abdominal and thoracic paragangliomas (pheochromocytomas). In this study, we aimed to establish paraganglioma risk in 101 asymptomatic germline mutation carriers and evaluate the results of our surveillance regimen. Asymptomatic carriers of an SDHD or SDHB mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 10 publications
4
35
0
Order By: Relevance
“…One retrospective study that corrected for ascertainment bias and missing pedigree information estimated that the penetrance of SDHB mutation was 21% by age 50 years and 42% by age 70 years similar to a large study with 673 SDHB carriers that estimated penetrance to be 22–24% by 60 years and 30.6% by age 80 years . Surveillance studies using magnetic resonance imaging (MRI) have shown that 12–18% of asymptomatic SDHB carriers developed PPGL within 4–9 years, further supporting lower penetrance .…”
Section: Clinical Characteristics (See Table  For a Summary)mentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective study that corrected for ascertainment bias and missing pedigree information estimated that the penetrance of SDHB mutation was 21% by age 50 years and 42% by age 70 years similar to a large study with 673 SDHB carriers that estimated penetrance to be 22–24% by 60 years and 30.6% by age 80 years . Surveillance studies using magnetic resonance imaging (MRI) have shown that 12–18% of asymptomatic SDHB carriers developed PPGL within 4–9 years, further supporting lower penetrance .…”
Section: Clinical Characteristics (See Table  For a Summary)mentioning
confidence: 99%
“…showed that 59% of 41 asymptomatic SDHD carriers had a head and neck PGL upon screening with MRI. In addition, six carriers developed symptoms suggestive of a PGL that could later be detected with MRI .…”
Section: Clinical Characteristics (See Table  For a Summary)mentioning
confidence: 99%
“…PGL paraganglioma, PCC, phaeochromocytoma, Abdo PGL abdominal paraganglioma, HNPGL head & neck paraganglioma. * Based on studies including: Astuti 2003, Neumann 2004, Benn 2006, Timmers 2007, Solis 2009, King 2011, Ayala‐Raimez 2011, Rijken 2016, Jasperson 2014, Papathomas 2015, Daniel 2016, Eijkelenkamp 2014, Tufton 2016, Niemeijer 2017; **Astuti 2001, Cascon 2002, Neumann 2002, Neumann 2004, Astuti 2003, Dannenberg 2005, Simi 2005, Benn 2006, Fish 2007, Havekes, 2007, Timmers 2008, Mannelli 2009, Neumann 2009, Heesterman 2013, Miederer 2013, Papathomas 2015, Daniel 2016 [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Surveillance Programmesmentioning
confidence: 99%
“…43,98 However, they can cause significant morbidity by virtue of their proximity to critical neural and vascular structures in the brain and neck, including the carotid artery, jugular vein, and cranial nerves (CNs) VII-XII. In this regard, the most common presenting symptoms include pain, dysphagia, hoarseness, pulsatile tinnitus, and conductive hearing loss.…”
mentioning
confidence: 99%